Does routine surveillance imaging after completing treatment for childhood solid tumours cause more harm than good? A systematic review and meta-analysis protocol - Jessica E. Morgan; Melissa Harden; Robert S. Phillips (Systematic Reviews, 2019)
Abstract Background This systemic review aims to synthesise the current literature surrounding off-therapy surveillance imaging in children and young people with extra-cranial solid tumours, with a view to establishing if routine imaging studies after treatment for childhood cancer increase overall survival, increase the psychological distress caused to patients and families, result in other harms to patients and are cost-effective strategies. Within this manuscript, we also describe how patient and public involvement has impacted upon the protocol. Methods The search will cover thirteen different databases, key conference proceedings and trial registers, as well as reference lists and forward citations of included papers. Prominent authors/clinicians in the field will be contacted. A full search strategy is provided. The study designs to be included in the review will be added in an iterative way (RCTs, quasi-randomised trials, prospective cohorts and retrospective cohorts). Qualitative studies will also be eligible for inclusion. We will include studies which examine a programme of surveillance imaging that aims to detect relapse in children or young people up to age 25 years who have completed treatment for a malignant extracranial solid tumour and have no evidence of active and ongoing disease at end of treatment. The primary outcome is overall survival, with secondary outcomes including psychological distress indicators, number of imaging tests performed, other harms of imaging and cost-effectiveness measures. Studies will be screened and data extracted by two researchers. Studies will be critically appraised using a stratified version of the ROBINS-I tool. Where appropriate, data will be synthesised using a random effects meta-analysis. A detailed analysis plan, including assessment of heterogeneity and publication bias, is provided. Discussion The aim of routine surveillance imaging is to detect recurrence of disease before clinical symptoms and signs develop. Some studies have suggested that most relapses of childhood cancer are detected due to clinical symptoms or signs, particularly in those with extra-cranial solid tumours, and when these relapses are detected by imaging, there is no increase in survival. This review aims to establish whether routine surveillance imaging is beneficial, as well as evaluating the potential negative impacts of surveillance programmes. Systematic review registration PROSPERO CRD42018103764